My People, My Country: A New Interpretation of Chinese Main Melody Film in the New Era - Xinyue, Xu; Jing, Hua (International Journal of Linguistics, Literature and Translation, 2020)
The Chinese film “My people, My country” runs through the historical process of the seventy years since the founding of New China. The film adopts a segmented narrative approach and successfully expresses the grand theme of national development through the stories of seven small characters. This paper provides a detailed analysis of “My people, My country” in terms of its narrative structure, narrative perspective and detail treatment. It is found out that the fragmented narratives, the individuals being the narrative center and the detailed historic setting in “My people, My country” all combined to offer a new interpretation for the main melody movies.